Literature Review: Comparison of Caron Process and RKEF On The Processing of Nickel Laterite Ore For Battery - Muhamad Alfa Rizky; Untung Sukamto; Agris Setiawan (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2022)
Indonesia has abundant resources, especially in natural resources (SDA), one of which is nickel. Nickel is a metal that is loved by many people because of the rapid development of technology in creating electric transportation, in particular, the application of nickel is one of the batteries. Nickel resources in the world are available in the form of Nickel Oxide as much as 60% and the remaining 40% is available in the form of sulfide reserves. Currently, there are 2 extraction methods, namely hydrometallurgy (Caron Process) and pyrometallurgy (Rotary Kiln Electric Furnace). Hydrometallurgy is a process used for nickel ore that has a grade of < 1.5%, while pyrometallurgy is still used for nickel ore that has a Ni content of < 3%. At present, the most common hydrometallurgical process is applied to limonite nickel ore. While the extraction process in pyrometallurgy uses saprolite nickel ore. Nickel metal processing, currently the best and the cheapest in terms of production costs is the hydrometallurgical process followed by the pyrometallurgical process. Using low-grade nickel is more suitable for manufacturing battery manufacture. The reason is that the Limonite Nickel reserves are more and can increase the selling value of the nickel ore. Thus, it is necessary to pay attention to the development in the processing process to increase the purity of the nickel-metal itself.